Performance of the Surgical Pleth Index and Analgesia Nociception Index in Healthy Volunteers and Parturients - Choi, Byung-Moon; Shin, Hangsik; Lee, Joo-Hyun; Bang, Ji-Yeon; Lee, Eun-Kyung; Noh, Gyu-Jeong (Frontiers in Physiology, 2021)
Various commercially available nociception devices have been developed to quantify intraoperative pain. The Surgical Pleth Index (SPI) and Analgesia Nociception Index (ANI) are among the analgesic indices that have been widely used for the evaluation of surgical patients. This study aimed to evaluate the clinical performance of the SPI and ANI in conscious healthy volunteers and parturients. Ten healthy volunteers and 10 parturients participated in this study. An algometer was used to induce bone pain in the volunteers until they rated their pain as 5 on the numerical rating scale (NRS); this procedure was repeated during the administration of remifentanil or normal saline. The study comprised two periods, and the volunteers were infused with different solutions in each period: normal saline during one period and remifentanil during the other in a randomized order. The parturients’ SPI and ANI data were collected for 2 min when they rated their pain levels as 0, 5, and 7 on the NRS, respectively. Both the SPI and ANI values differed significantly between NRS 0 and NRS 5 (P<0.001) in the volunteers, irrespective of the solution administered (remifentanil or normal saline). At NRS 5, the SPI showed similar values, irrespective of remifentanil administration, while the ANI showed significantly lower values on remifentanil administration (P=0.028). The SPI and ANI values at NRS 5 and NRS 7 did not differ significantly in the parturients (P=0.101 for SPI, P=0.687 for ANI). Thus, the SPI and ANI were effective indices for detecting pain in healthy volunteers and parturients.